(untitled) - Lowenthal, Julian (New York, 2002)
The financial services industry is constantly changing and you need to respond. Change is a constant in the financial services industry (FSI). The question is, "What should you do to survive?" Whether you work in or sell to the industry, you'll benefit from the in-depth insight, professional knowledge, and practical tools found in J.K. Lasser Pro Survival Skills in Financial Services.
Keywords: Financial services industry,Selling,Công nghiệp dịch vụ tài chính,Sự bán (Hàng hóa)